Codes correcting key errors - Das, Pankaj Kumar (TWMS journal of applied and engineering mathematics, 2015)
The objective of coding theory is to protect a message going through a noisy channel. The nature of errors that cause noisy channel depends on different factors. Accordingly codes are needed to develop to deal with different types of errors. Sharma and Gaur [6] introduced a new kind of error which is termed as 'key error'. This paper presents lower and upper bounds on the number of parity-check digits required for linear codes capable of correcting such errors. An example of such a code is also provided.